A Review of Experiences on the use of Nitrogen in Czech Coalmines - Ing. Alois Adamus; Ing. Lubomír Hájek; Ing. Václav Pošta (Society for Mining, Metallurgy & Exploration, 1995)
This paper reviews experiences connected with the use of nitrogen in the Czech coal industry. Special attention is focused on the first use nitrogen In the Czech Republic, it is probably the first case of fighting a mine fire using nitrogen in all the World. Discussion dwells on the present-day use of nitrogen, its sources, consumption, technological equipment, and the theoretical evaluation of nitrogen flushing.